2004
DOI: 10.1177/0011000004269300
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Research for the Liberation of Battered Women

Abstract: Domestic violence interferes with women's exploration of career interests

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
(58 reference statements)
0
27
0
Order By: Relevance
“…In response to the economic abuse that many abused women experience, CCR services have extended to contracting with local businesses in hopes of finding victims a place of employment in the short term and, in the long run, economic independence (Chronister, Wettersten, & Brown, 2004). Further, CCR programs may attempt to disseminate information about domestic violence to local employers in an effort to make them aware of this enormous social problem.…”
Section: Coordinated Community Response (Ccr)mentioning
confidence: 99%
“…In response to the economic abuse that many abused women experience, CCR services have extended to contracting with local businesses in hopes of finding victims a place of employment in the short term and, in the long run, economic independence (Chronister, Wettersten, & Brown, 2004). Further, CCR programs may attempt to disseminate information about domestic violence to local employers in an effort to make them aware of this enormous social problem.…”
Section: Coordinated Community Response (Ccr)mentioning
confidence: 99%
“…Some researchers may feel that their personal safety could be compromised by carrying cash or gift vouchers for particular research projects. Chronister, Wettersten, and Brown (2004), writing on payment to participants in studies of domestic violence, advocate that cheques are not given as the participant may be not be in control of her personal finances.…”
Section: Practical Issues When Making Paymentsmentioning
confidence: 99%
“…Using quantitative methods, Chronister (2007), Chronister, Wettersten, and Brown (2004), and Brown, Reedy, Fountain, Johnson, and Dichiser (2000) examined the perceived vocational barriers and supports of women survivors living in the community and shelters. The authors found racial group differences in women's perceptions of vocational barriers and supports and significant relationships between barriers and supports perceptions and other cognitive variables (e.g., outcome expectations, external expectancies, and self-efficacy).…”
Section: Domestic Violence and Vocational Researchmentioning
confidence: 99%